Clonal and sanitary selection in stone fruits - Savino V.; Di Terlizzi B.; Audergon J.-M. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
Clonal and sanitary selection in stone fruits was briefly discussed. The objectives of clonal and sanitary selection were separately described. The establishment of a multidisciplinary technical team composed of pomologists and plant pathologists, was considered as an essential condition for the implementation of the selection. The different phases of selection and the conditions of conservation for the selected clones were also discussed.